2020
DOI: 10.1111/1365-2745.13567
|View full text |Cite
|
Sign up to set email alerts
|

Mosses reduce soil nitrogen availability in a subarctic birch forest via effects on soil thermal regime and sequestration of deposited nitrogen

Abstract: 1. In high-latitude ecosystems bryophytes are important drivers of ecosystem functions. Alterations in abundance of mosses due to global change may thus strongly influence carbon (C) and nitrogen (N) cycling and hence cause feedback on climate. The effects of mosses on soil microbial activity are, however, still poorly understood. Our study aims at elucidating how and by which mechanisms bryophytes influence microbial decomposition processes of soil organic matter and thus soil nutrient availability. 2. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 77 publications
(100 reference statements)
0
13
3
Order By: Relevance
“…Contrary to rst hypothesis, soils at moss-grown sites exhibited relatively high microbial biomass N, dissolved N and potential enzyme activities (Fig. 4 and Table 3), which contrasts with ndings of our previous study in a nearby birch forest, where we observed a negative effect of the moss layer on soil N availability (Koranda and Michelsen 2021). This apparent discrepancy shows that the in uence of mosses on soil microbial processes and nutrient cycling is context-speci c, depending on the factors most strongly regulating soil microbial activity in the respective ecosystem: While in the birch forest, characterized by a homogenous understorey and SOM quality, the insulating effect of the moss layer was a crucial factor for soil microbial activity (Koranda and Michelsen 2021), in tundra heath the high spatial variability in plant traits, SOM quality and soil pH mainly determined microbial community structure and nutrient availability, whereas soil temperature was comparatively less relevant.…”
Section: Effects Mosses On Microbial Decomposition Processes and Soil...contrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to rst hypothesis, soils at moss-grown sites exhibited relatively high microbial biomass N, dissolved N and potential enzyme activities (Fig. 4 and Table 3), which contrasts with ndings of our previous study in a nearby birch forest, where we observed a negative effect of the moss layer on soil N availability (Koranda and Michelsen 2021). This apparent discrepancy shows that the in uence of mosses on soil microbial processes and nutrient cycling is context-speci c, depending on the factors most strongly regulating soil microbial activity in the respective ecosystem: While in the birch forest, characterized by a homogenous understorey and SOM quality, the insulating effect of the moss layer was a crucial factor for soil microbial activity (Koranda and Michelsen 2021), in tundra heath the high spatial variability in plant traits, SOM quality and soil pH mainly determined microbial community structure and nutrient availability, whereas soil temperature was comparatively less relevant.…”
Section: Effects Mosses On Microbial Decomposition Processes and Soil...contrasting
confidence: 99%
“…Potential hydrolytic enzyme activities were estimated by microplate assays using uorescent substrates, as described in detail in Koranda and Michelsen (2021). Soil slurries were prepared using Na-acetate buffer (pH 5.7).…”
Section: Extracellular Enzyme Activitiesmentioning
confidence: 99%
“…Biocrusts are ecosystem engineers at the atmosphere–soil interface, and they regulate a wide range of ecosystem functions, including C budgets (Dacal et al, 2020; García‐Palacios et al, 2018), nitrogen (N) cycles (Koranda & Michelsen, 2021; Maier et al, 2021), phosphorus (P) cycles (Kurth et al, 2021), hydrological processes (Eldridge et al, 2020), soil thermal properties (Xiao, Ma, et al, 2019) and soil stability (Algayer et al, 2014). Specifically, biocrusts regulate soil CO 2 flux not only directly through photosynthesis (Li, Hui, et al, 2021) and respiration (Guan et al, 2021, 2022) but also indirectly by altering the soil temperature (Xiao, Ma, et al, 2019), moisture (Eldridge et al, 2020), N availability (Koranda & Michelsen, 2021) and microbial community and functional structure (Wang, Wang, et al, 2021). For example, soil respiration at microsites with high biocrust coverage is significantly higher than that at microsites with low biocrust coverage (Escolar et al, 2015; Maestre et al, 2013) or in bare soils (Morillas et al, 2017; Yao et al, 2020), and biocrusts can contribute to more than 40% of CO 2 flux via soil respiration (Castillo‐Monroy et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As structural components of drylands, biocrusts are soil surface communities dominated by cyanobacteria, algae, lichens and mosses (Belnap et al, 2016), and they cover ~30% of the dryland soil surface (Rodriguez‐Caballero et al, 2018). Biocrusts are ecosystem engineers at the atmosphere–soil interface, and they regulate a wide range of ecosystem functions, including C budgets (Dacal et al, 2020; García‐Palacios et al, 2018), nitrogen (N) cycles (Koranda & Michelsen, 2021; Maier et al, 2021), phosphorus (P) cycles (Kurth et al, 2021), hydrological processes (Eldridge et al, 2020), soil thermal properties (Xiao, Ma, et al, 2019) and soil stability (Algayer et al, 2014). Specifically, biocrusts regulate soil CO 2 flux not only directly through photosynthesis (Li, Hui, et al, 2021) and respiration (Guan et al, 2021, 2022) but also indirectly by altering the soil temperature (Xiao, Ma, et al, 2019), moisture (Eldridge et al, 2020), N availability (Koranda & Michelsen, 2021) and microbial community and functional structure (Wang, Wang, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mosses are a species‐rich clade found in almost all terrestrial ecosystems from the Arctic to the tropics (Geffert et al, 2013), with an often large impact on the carbon (C) and nitrogen (N) cycle (Elbert et al, 2012; Koranda & Michelsen, 2021). They live on soils, rocks and bark of living or dead trees under sometimes extreme climatic and nutrient‐poor conditions (Dierssen, 2001; Müller et al, 2020).…”
Section: Introductionmentioning
confidence: 99%